The Training of Design Thinking Process in New Product Development - I Made Aryata; I Gede Marendra; Irmawan Afgani (PT FORMOSA CENDEKIA GLOBAL, 2023)
The current era of globalization has made technological developments faster, which has forced manufacturers to be able to present innovations in the products they produce that can answer customer needs. The Design Thinking Process is an iterative process in which we seek to understand the user to identify the right strategy. To answer this challenge, Design Thinking Process training was conducted for UNSERA Industrial Engineering Students. From the results of the training conducted, the participants already knew about Design Thinking, the steps for implementing Design Thinking, and the implementation of Design Thinking in several industries that support problem-solving.